Relationship between KLSE composite index and other major indices / Ibrahim Ab. Rahman - Ab. Rahman, Ibrahim (1995)
The main objective of this study is to determine^ whether there is any relationship between Kuala Lumpur Composite Index and other major world indices. The selected bourses and indices are Tokyo Stock Exchange (Nikkei ), Hong Kong Stock Exchange ( Hang Seng ), New York Stock Exchange ( Dow Jones Industrial Average ), London Stock Exchange ( FT:SE 100 ), and Stock Exchange of Singapore (SES All Shares ). A brief background of the selected bourses and computation of the indices were carried out in chapter two. Chapter three continue with the literature review from the previous studies which are considered as related to this study. Chapter four continued with the data and methodology. The data collected were the weekly closing indices of the selected indices for a period of five years from January 1989 to December 1993. There were 260 observations of closing indices for each selected indices. There are five hypotheses postulated in order to conduct a simple linear regression and correlation analysis by using the Statistical Package for Social Science (SPSS ). From the analysis carried out it can be concluded that Kuala Lumpur Composite Index is positively related to Nikkei, Hang Seng, Dow Jones Industrial Average, FT-SE 100 and SES All Shares index. However the degree of correlations is weak, except for SES All Shares which shows a strong relationship with correlation coefficient of 0.7222. Therefore it can be concluded that information on performance of other major bourses should be considered in making investment decision in Kuala Lumpur Stock Exchange.